THE ROLE OF UNICEF IN ADDRESSING THE HIV/AIDS EPIDEMIC IN TANZANIA FROM 2019-2022 - Budiman, Imam; Syallsabila, Annisa; Maharani, Jihan; Kawuwung, Lara; Liani , Selvi Raya; Himawan, Syahnaz Nur Aulia (Sean Institute, 2023)
The transmission of the HIV/AIDS virus in Tanzania to mothers, babies, and children has become a global problem that has attracted world attention. These threats must be a primary focus to ensure the well-being and security of the next generation. This study uses literature studies with the theory of securitization and international organizations in answering research questions about the phenomena studied. As a securitization actor, UNICEF made a statement through the Children and AIDS program to tackle the spread of HIV/AIDS in Tanzania. Seeing that the Tanzanian government was unable to overcome the spread of this virus, the government chose to work with UNICEF in the hope that the collaborative program created would be able to overcome the spread of HIV and AIDS. The results of the study show that the implementation of the program indicates progress toward public awareness in Tanzania, especially among those living with HIV/AIDS themselves. Not only that, UNICEF has aided in every field and aspect of Tanzania. But of course, there are challenges in implementing a program in a country, one of which is discrimination which can hinder the planned program.